2021
DOI: 10.1111/jmwh.13280
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Influences on Young Women's Choice to Use Long‐Acting Reversible Contraception: A Systematic Review

Abstract: Introduction: Long-acting reversible contraception (LARC; including intrauterine devices and implants) is recommended as the first-line contraceptive choice by several professional organizations (eg, American College of Obstetricians and Gynecologists); however, rates of uptake are lower than those of other contraceptive methods. A young woman's social network may influence the decision to use LARC. The purpose of this review was to determine the role of health care providers (HCPs), family, peers, and sexual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…In addition, family and friends' perspectives of contraception may influence contraceptive selection and continuation. A recent review of the impact of social networks on contraceptive use found that families were more likely to disseminate inaccurate or negative information about LARC [23]. This highlights the importance for healthcare providers to identify strategies to dispel negative information consistently.…”
Section: Interpersonal-level Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, family and friends' perspectives of contraception may influence contraceptive selection and continuation. A recent review of the impact of social networks on contraceptive use found that families were more likely to disseminate inaccurate or negative information about LARC [23]. This highlights the importance for healthcare providers to identify strategies to dispel negative information consistently.…”
Section: Interpersonal-level Factorsmentioning
confidence: 99%
“…• Supportive relationships from parents, friends, and healthcare professionals [23,32] • Trust of provider [23,29] Institutional…”
Section: Individualmentioning
confidence: 99%
“…13 Patients make contraceptive decisions informed by the recommendation of medical professionals, but also with the input of partners, friends, family, and social media networks. [14][15][16][17][18] Yet little is known about the contraceptive information sources valued by individuals with OUD. As such, we sought to understand patient perspectives on trusted sources of contraception information for pregnancy-capable individuals with OUD.…”
Section: Introductionmentioning
confidence: 99%
“…Patients make contraceptive decisions informed by the recommendation of medical professionals, but also with the input of partners, friends, family, and social media networks 14–18 . Yet little is known about the contraceptive information sources valued by individuals with OUD.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 While their efficacy and safety are well known, limited data are available on the factors associated with using LARC. 9,12 While six in 10 women in the United States have an ongoing or potential need for contraceptive services, 13 currently published data on the topic have several limitations, including limited information regarding factors associated with LARC usage 9 and focusing on barriers in specific age populations such as adolescents [14][15][16] or during the postpartum period. 17,18 Given these shortcomings, and to potentially decrease the rate of unintended pregnancies, an understanding of the usage of reliable methods of contraception is warranted.…”
Section: Introductionmentioning
confidence: 99%